From moths to caterpillars: Ideal conditions for Galleria mellonella rearing for in vivo microbiological studies - Jorjão, Adeline L. [UNESP]; Oliveira, Luciane D. [UNESP]; Scorzoni, Liliana [UNESP]; Figueiredo-Godoi, Lívia Mara A [UNESP]; Cristina A Prata, Marcia; Jorge, Antonio Olavo C [UNESP]; Junqueira, Juliana C. [UNESP] (Taylor & Francis, 2018)
Galleria mellonella is a well-accepted insect model for the study of pathogen-host interactions and antimicrobial compounds. The main advantages of this model include the low cost of maintenance, the fast life cycle, the possibility of using a large number of caterpillars and the innate immune system, which is evolutionarily conserved relative to mammals. Because of these advantages, different research groups have been working to implement the rearing of G. mellonella in laboratory conditions. This protocol describes our experience in the rearing of G. mellonella caterpillars for experimental infection models and the influence of different artificial diets on developmental and physiological parameters. Here, we suggest a diet composition that benefits the life cycle of G. mellonella by accelerating the larval phase length and increasing the caterpillar weight. This diet also stimulated the immune system of G. mellonella by increasing the hemolymph volume and hemocyte concentration. In addition, our rearing protocol generated caterpillars that are more resistant to infection by Staphylococcus aureus, Escherichia coli and Candida albicans. A standard G. mellonella rearing protocol is fundamental to minimize external influences on the results, and this simple and easy protocol can support researchers starting to rear G. mellonella.
Keywords: experimental model; Galleria mellonella; in vivo study; rearing